(NpOSLEDNIJ dOZOR (B((NdOZORY (B#4)s - Sergei Lukyanenko (Moscow (NiZDATELXSTWO asts, 2006)
(NsU]ESTWUET LI KONEC pUTI(B? (NwOZMOVEN LI KONEC bORXBY ^ELOWEKA S SAMIM SOBOJ I OKRUVA@]IM MIROM(B? (NnA \TI I MNOGIE DRUGIE WOPROSY sERGEJ lUKXQNENKO DAET OTWETY W SWOEJ NOWOJ KNIGE(B. "(NpOSLEDNIJ dOZOR(B" - (N\TO PUTE[ESTWIE S LU^[IM ROSSIJSKIM FANTASTOM W POISKAH NOWOJ ISTINY(B. (NnO BUDXTE OSTOROVNY(B: (NsERGEJ lUKXQNENKO NE L@BIT PROSTYH RE[ENIJ I KOROTKIH DOROG(B. (NtAK ^TO PRIKL@^ENIE OBE]AET BYTX QRKIM I ZAMAN^IWYM(B. (NkAK SAMA VIZNX(B, (NS RAZNOOBRAZIEM KOTOROJ MOVET SRAWNITXSQ TOLXKO FANTASTIKA (B"(NpOSLEDNEGO dOZORA(B". (Nw pUTX(B?!s
Keywords: Fantasy; Fiction; Horror; Science Fiction